Management of information security - Whitman, Michael E.; Mattord, Herbert J. (Australia : Cengage Learning Asia Pte Ltd, 2014)
Beginning with the foundational and technical components of information security, this title focuses on access control models, information security governance, and information security program assessment and metrics.
1. Introduction to Management of Information Security -- 2. Planning for Security -- 3. Planning for Contingencies -- 4. Information Security Policy -- 5. Developing the Security Program -- 6. Security Management Models -- 7. Security Management Practices -- 8. Risk Management: Identifying and Assessing Risk -- 9. Risk Management: Controlling Risk -- 10. Protection Mechanisms -- 11. Personnel and Security -- 12. Law and Ethics.
Includes index.
Keywords: COMPUTER SECURITY -- MANAGEMENT